2021
DOI: 10.33314/jnhrc.v18i4.2896
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Drug in Health Facilities: A Cross-sectional Study

Abstract: Background: Poor quality drugs result minor to detrimental effect on human health. The drug should be of standard quality and should be used appropriately in order to meet its therapeutic efficacy. This study aims to assess the quality of drug in Nepal. Methods: A cross sectional study was conducted in randomly selected 88 health facilities in Nepal from 10th April to 30th June 2016. Selective medicines were collected from both private licensed pharmacies and selected public health facilities. Face to face int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…al. [ 14 ] and Karki KB et al [ 15 ] also identified 32.5% (out of 40 brands) and 4.21% (out of 214 samples) substandard drugs respectively in Nepal. Thus, the availability of substandard medicines in Nepal suggests for the improvement in the national regulatory system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al. [ 14 ] and Karki KB et al [ 15 ] also identified 32.5% (out of 40 brands) and 4.21% (out of 214 samples) substandard drugs respectively in Nepal. Thus, the availability of substandard medicines in Nepal suggests for the improvement in the national regulatory system.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of substandard medicines in the pharmaceutical market of Nepal has been a concern for many years. Several studies and investigations have found evidence of substandard medicines being sold in Nepal [ 14 , 15 ]. Studies have found substandard medicines in a range of therapeutic areas, including antibiotics, which can lead to treatment failure, drug resistance, and adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…The country's basic healthcare delivery is facilitated by unqualified conventional practitioners and medicine distributors, lacking official professional qualifications or trainings. This situation led to irrational dispensing of antimicrobials, often in situations when they are unnecessary [7,8]. The pharmacies and medical stores in Nepal operate under the regulations outlined in the Drug Act of 1978 [9].…”
Section: Introductionmentioning
confidence: 99%